First documented record for the Rufous Collared Sparrow Zonotrichia capensis (Aves: Emberizidae) in the Peruvian Amazon - Ugarte, Mauricio (2018)
We report the presence of the Rufous Collared Sparrow Zonotrichia capensis for the first time in the departments of Loreto and San Martín at 155 and 240 m altitude respectively, which corresponds to the first confirmed record of the species for the Peruvian Amazon. It is possible that the presence of the species is due to the existence of the Tarapoto - Yurimaguas road, which would facilitate the occupation of the species by landscape transformation.